2016
DOI: 10.18805/ar.v37i2.10736
|View full text |Cite
|
Sign up to set email alerts
|

Role of silicon under water deficit stress in wheat: (Biochemical perspective): A review

Abstract: Silicon's role in mediating resistance against various stresses has been a matter of focus in the past decade. Poaeceae family plants are known as high accumulators of silicon. Wheat shows rapid absorption, the optimum accumulation of silicon occurring at around 20 days. Silicon plays a role as a mechanical and a physiological barrier. It also alters the levels of osmolytes and antioxidant enzymes which are a first line of defense in the water deficit stress; also reducing the levels of oxidative stress factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
4
10
0
Order By: Relevance
“…As was reflected in its additive effect on proline accumulations, Si altered the biochemical composition of potato tissues making the plant more resistant to heat stress under water deficit conditions. This is in agreement with the previous work, which demonstrated the role of proline in offsetting the adverse effects of water deficit thereby conferring stress tolerance (Sapre and Vakharia, 2016). Other studies have verified that proline concentrations in potato leaves increase with increase in Si concentrations under waterdeficit conditions, which indicates that silicon may be associated with plant osmotic adjustment (Crusciol et al, 2009;Farhad et al, 2011;Pilon et al, 2014).…”
Section: Effect Of Silicon Application On Potato Growth Physiology Asupporting
confidence: 91%
“…As was reflected in its additive effect on proline accumulations, Si altered the biochemical composition of potato tissues making the plant more resistant to heat stress under water deficit conditions. This is in agreement with the previous work, which demonstrated the role of proline in offsetting the adverse effects of water deficit thereby conferring stress tolerance (Sapre and Vakharia, 2016). Other studies have verified that proline concentrations in potato leaves increase with increase in Si concentrations under waterdeficit conditions, which indicates that silicon may be associated with plant osmotic adjustment (Crusciol et al, 2009;Farhad et al, 2011;Pilon et al, 2014).…”
Section: Effect Of Silicon Application On Potato Growth Physiology Asupporting
confidence: 91%
“…The data indicate that the reduction of NPK fertilizer dosages up to 50% did not significantly affect the growth performances of Detam-1 black soybean. These evidences confirm the assumption that Si promotes a healthy plant especially in combating water stress as reported by many researchers (Heckman, 2013;Chanchal et al 2016;Sapre and Vakharia 2016). Addition of Si did also induce the Si uptake as indicated by increasing Si leaf content.…”
Section: Effect Of Bio-nano Osa On Plant Growthsupporting
confidence: 88%
“…In addition, silicon plays a role as a mechanical and a physiological barrier. It also alters the levels of osmolytes and antioxidant enzymes which are the first line of defense in drought stress, also reducing the levels of oxidative stress factors such as hydrogen peroxide (Sapre and Vakharia, 2016). These results are harmony with those obtained with Abd El-Gawad et al (2017) on potato they showed that irrigation after the depletion of 55-60 % of available soil water and spraying with potassium silicate at 2000 ppm gave the highest values of leaf area, fresh and dry weight of shoots than other interaction treatments.…”
Section: Effect Of the Interactionmentioning
confidence: 99%